A consistent and potentially exploitable response during chondrogenesis of mesenchymal stem cells from osteoarthritis patients to the protein encoded by the susceptibility gene GDF5. - Madhushika Ratnayake; Maria Tselepi; Robert Bloxham; Frank Plöger; Louise N Reynard; John Loughlin (PLoS ONE)
Osteoarthritis (OA) is a common joint disease characterised by the focal loss of the protective cartilage layer at the ends of the bones. It is painful, disabling, multifactorial and polygenic. The growth differentiation factor 5 gene GDF5 was one of the first reported OA susceptibility signals that showed consistent association to OA, with the transcript single nucleotide polymorphism (SNP) rs143383 demonstrating association in Asians and Europeans. The functional effect of the signal is reduced expression of the gene. The GDF5 protein is an extracellular matrix signalling molecule that is active during chondrogenesis and in mature chondrocytes. Due to the functional impact of the susceptibility, we previously assessed the effect of supplementing chondrocytes from OA patients with exogenous GDF5. Their response was highly discordant, precluding the application of GDF5 as a simple means of attenuating the genetic deficit. Since GDF5 is also active during development, we have now assessed the effect of exogenous GDF5 on bone marrow derived mesenchymal stem cells (MSCs) that are undergoing chondrogenesis during cartilage disc formation. MSCs from healthy donors and OA patients were studied and the effect of GDF5 was assessed by measuring the wet mass of the discs, by histological staining, and by monitoring the change in expression of anabolic, catabolic and hypertrophic protein-coding genes. The MSCs expressed the three principal GDF5 receptor genes and responded in a significantly anabolic manner (increase in wet mass, p = 0.0022; Bonferroni corrected p = 0.018) to a variant form of GDF5 that targets the most abundantly expressed receptor, BMPR-IA. GDF5 elicited significant (p < 0.05) changes in the expression of anabolic, catabolic and hypertrophic genes with several consistent effects in healthy donors and in OA patients. Our data implies that, unlike OA chondrocytes, OA MSCs do respond in a predictable, anabolic manner to GDF5, which could therefore provide a route to modulate the genetic deficit mediated by the rs143383 association signal.